Inositol 1,4,5-trisphosphate receptor subtype 3 in pancreatic islet cell secretory granules revisited. - Ravazzola, M (1996)
It has been reported that the inositol 1,4,5-trisphosphate receptor subtype 3 is expressed in islet cells and is localized to both insulin and somatostatin granules [Blondel, O., Moody, M. M., Depaoli, A. M., Sharp, A. H., Ross, C. A., Swift, H. & Bell, G. I. (1994) Proc. Natl. Acad. Sci. USA 91, 7777-7781]. This subcellular localization was based on electron microscope immunocytochemistry using antibodies (affinity-purified polyclonal antiserum AB3) directed to a 15-residue peptide of rat inositol trisphosphate receptor subtype 3. We now show that these antibodies cross-react with rat, but not human, insulin. Accordingly, the anti-inositol trisphosphate receptor subtype 3 (AB3) antibodies label electron dense cores of mature (insulin-rich) granules of rat pancreatic beta cells, and rat granule labeling was blocked by preabsorption of the AB3 antibodies with rat insulin. The immunostaining of immature, Golgi-associated proinsulin-rich granules with AB3 antibodies was very weak, indicating that cross-reactivity is limited to the hormone and not its precursor. Also, the AB3 antibodies labeled pure rat insulin crystals grown in vitro but failed to stain crystals grown from pure human insulin. By immunoprecipitation, the antibodies similarly displayed a higher affinity for rat than for human insulin. We could not confirm the labeling of somatostatin granules using AB3 antibodies.